Factors that influence the use of accounting information in Micro, Small, and Medium Enterprises (MSMEs) in Medan City - Clarisa Clarisa; Hendra Wijaya (University of Merdeka Malang, 2022)
MSMEs play a substantial role in increasing GDP and employment in Indonesia. However, there are still many MSMEs who have not utilized the use of accounting information in running their business. The use of accounting information can help them to maintain their business sustainability. During this pandemic era, many MSMEs were affected, including the MSMEs in the Province of North Sumatera. In May 2020, the provincial government of North Sumatra recorded that 672.000 MSMEs were affected by the pandemic. The province's capital city is Medan, where the government of Medan city also really supports the development of MSMEs in Medan. So, the research aims to examine and analyze the effect of business age, educational level, business scale, and accounting training on using accounting information in MSMEs in Medan city. This research used primary data, which was obtained by distributing both physical and google form questionnaires. The method of sampling used in this research is purposive and convenience sampling. There are 109 data processed and analyzed using the multiple linear regression method, where the ordinal data is transformed into intervals using the Method of Successive Interval (MSI). From the results, the business scale and accounting training both significantly positively affect the use of accounting information in MSMEs in Medan City during the business age, and educational level does not affect the use of accounting information in MSMEs in Medan City.